Building the business development strategy for broccoli kindergarten = Xây dựng chiến lược phát triển kinh doanh Trường Mần non Tư thục Bông Cải Xanh - Nguyễn, Thanh Loan (2020)
Systemize the basic theories about business strategy to develop a new business and the basic theories about preschool activities. Proposing to develop a business strategy to develop a private kindergarten combining the US training program and the Steiner educational method. Proposing the development of functional strategies for the development of private preschools based on the proposed overall business strategy for practical readiness.